Effects of the COVID-19 pandemic on urban residents’ consumption behavior of forest food—an empirical study of 6,946 urban residents - Liu, Shiyu; He, Dan; Chen, Ke (Frontiers in Sustainable Food Systems, 2023)
Forest food, which possesses enormous potential, has emerged as a significant and promising food source under the all-encompassing approach to food. The sudden outbreak of the COVID-19 pandemic in 2019 has enhanced health cognition among residents, impacting household food consumption patterns. In this study, we analyzed data from 6,946 urban households in 14 cities of Liaoning Province to examine the consumption behavior of urban households regarding 4 categories of forest food (forest nuts, forest fruits and vegetables, forest drinks, and forest medicines) before and after the COVID-19 pandemic. Various empirical methods were employed, including the Contingent Valuation Method (CVM), Ordinal Logit Model, Mediation Effect Model, and Moderation Effect Model. The results revealed that the COVID-19 pandemic positively impacted the “willingness-behavior” consumption behavior of urban residents toward forest food. Health cognition played a positive mediating role in influencing residents’ willingness to pay (WTP) for forest food during the pandemic. Per capita income had a negative moderating effect on the actual purchasing behavior of urban residents toward forest food. Furthermore, differences were observed in the consumption behavior of forest food among residents in cities with different levels of pandemic severity.